PHOTOGRAMMETRY FOR QUICK SURVEY IN EMERGENCY CONDITIONS: THE CASE OF VILLA GALVAGNINA - V. M. Nannei; F. Fassi; G. Mirabella Roberti (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
Photogrammetry is a survey method that provides good quality results also by using basic photographic equipment and user-friendly, low-cost software. The advantages of the image-based modelling techniques compared with the traditional topographic tools are very significant in emergencies, when the time for the survey is limited and many buildings are involved, as usually happens in case of relevant seismic events. The goal of this study is to verify the quality of the models obtained from quick digital images acquisition, carried out under non-optimal lighting condition and no accessibility of the building. As case of study was chosen the main front of Villa Galvagnina in Moglia, a Renaissance hunting palace badly damaged by the earthquake of May 20, 2012. The modelling was performed using two different software, Agisoft Metashape and 3DFlow Zephyr. This paper presents a comparison between the results obtained using different datasets; the workflow, the difficulties encountered during the survey and the data processing methods are fully described and discussed.